2017
DOI: 10.1186/s12966-017-0527-6
|View full text |Cite
|
Sign up to set email alerts
|

Associations between transition to retirement and changes in dietary intakes in French adults (NutriNet-Santé cohort study)

Abstract: BackgroundFew studies have focused on the influence of retirement on dietary behaviors. Our study aimed at assessing the associations between transition to retirement and changes in dietary intake in French adults, particularly according to spousal retirement and baseline income.MethodsThis prospective study included 577 French participants from the NutriNet-Santé cohort who retired over a 5-year follow-up (2009–2014 or 2010–2015). At baseline and every year, dietary intakes were assessed using 24 h records. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
5

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
(34 reference statements)
1
7
0
5
Order By: Relevance
“…A French study found that transition to retirement was associated with unhealthier dietary intakes such as a decrease in intake of fruits, proteins, and some vitamins as well as an increase in intakes of fatty and sweet products, saturated fatty acids, and sodium. Changes of dietary intakes with retirement were particularly marked in men with the lowest income at baseline ( Hassen et al, 2017 ). Another French longitudinal study reported that the amount of dietary nutrients consumed remained the same before and after retirement ( Lauque, Nourashemi, Soleilhavoup, Guyonnet, & Bertiere, 1998 ).…”
Section: Resultsmentioning
confidence: 99%
“…A French study found that transition to retirement was associated with unhealthier dietary intakes such as a decrease in intake of fruits, proteins, and some vitamins as well as an increase in intakes of fatty and sweet products, saturated fatty acids, and sodium. Changes of dietary intakes with retirement were particularly marked in men with the lowest income at baseline ( Hassen et al, 2017 ). Another French longitudinal study reported that the amount of dietary nutrients consumed remained the same before and after retirement ( Lauque, Nourashemi, Soleilhavoup, Guyonnet, & Bertiere, 1998 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have found an association between retirement and a change to unhealthier food habits. A French prospective study found that transition to retirement was associated with a decrease in fruit consumption and overall unhealthier dietary intakes (27) . Other studies have found positive changes, such as an increased consumption of vegetables after retirement in a French prospective cohort study (28) .…”
Section: Discussionmentioning
confidence: 99%
“…People who retire tend to decrease their food expenditures [5], while increasing cooking time [6]. The decrease in food expenditures leads to a higher intake of unhealthier, cheaper foods [7]. Thus, retirement has been considered as a risk factor for weight gain [8] but also for malnutrition [9].…”
Section: Introductionmentioning
confidence: 99%
“…Still, the impact of retirement on diet is unclear. Retirement has been associated with an improvement [11,12] or a worsening [7] on diet. Similarly, most reviews on the effect of retirement on diet failed to provide a definite conclusion [1,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation